Molecular detection of Strongyloides ratti in faecal samples from wild rats in Serdang, Malaysia - Al-Zihiry, Khalid Jameel Kadhim; Aliyu, Mahmuda; Atshan, Salman Sahab; Unyah, Ngah Zasmy; Ibraheem, Zaid Osama; Abd. Majid, Roslaini; Awang Hamat, Rukman; Abdullah, Wan Omar (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2015)
Purpose: To detect Strongyloides ratti in faecal samples using conventional methods and to confirm the identification using a sensitive and specific method, namely, polymerase chain reaction (PCR). Methods: A PCR method targeting the small subunit of the rRNA gene was performed in this study for the detection of DNA from Strongyloides ratti (an animal model of S. stercoralis) in faecal samples of wild Brown rats, Rattus norvegicus. Results: Strongyloides ratti was detected in 34.2 % of collected rats by different conventional techniques and confirmed by PCR. The essay presented 100 % sensitivity with Strongyloides universal primer. Conclusion: The findings of this study suggest that the application of PCR with universal primer is a very sensitive methodology to detect S. ratti in faecal material of wild rats infected even with very low parasite burden.